Industri Rumah Tangga Aren di Nagari Labuah Gunuang Kecamatan Lareh Sago Halaban Kabupaten Lima Puluh Kota (2000-2020) - Fachry, Ahmad Zaky; Asri, Zul (Jurnal Kronologi, 2025)
This study discusses the Sugar Palm Home Industry in Nagari Labuah Gunuang, Lareh Sago Halaban District, Lima Puluh Kota Regency in 2000-2020. The processing of sugar palm plants as a home industry in Nagari Labuah Gunuang has been carried out by the community since the time of their ancestors, even since the Dutch colonial era which continues to this day. The purpose of this study is to determine the development of the sugar palm home industry in Nagari Labuah Gunuang in 2000-2020. This study uses a historical research method with the following steps: heuristics, source criticism, interpretation, and historiography. The results of the study show that the sugar palm home industry in Nagari Labuah Gunuang has experienced changes and developments in terms of products and processing. Initially, the palm sugar home industry only produced molded palm sugar, along with the development of the times, the palm sugar industry in Nagari Labuah Gunuang experienced developments that began with the experiment of making palm sugar but was hampered by marketing so it stopped, which caused the community to return to processing molded palm sugar and start seriously planting and cultivating palm plants, then the emergence of the palm wine industry but in the end it was stopped by the government because it had a negative impact on the community, then the community returned to producing palm sugar until the government built a factory for processing palm sugar which was managed by a group of palm farmers in Jorong Talaweh and succeeded in producing products such as molded palm sugar, palm sugar and fresh sap as superior products as well as small block molded sugar products and liquid sugar were developed.